Durable left ventricular assist device as a bridge to recovery for addisonian crisis related cardiomyopathy. Issue 10 (11th September 2017) - Dimarakis, Ioannis; Shaw, Steven; Venkateswaran, Rajamiyer
Abstract: A 19‐year‐old female with addisonian crisis‐related cardiomyopathy underwent temporary mechanical circulatory support followed by insertion of a durable left ventricular assist device. Successful device explanation was possible 2.5 years following implantation.